Proceedings of the International Conference on Tourism, Economics, Accounting, Management, and Social Science (TEAMS 2018) 2019
DOI: 10.2991/teams-18.2019.3
|View full text |Cite
|
Sign up to set email alerts
|

Testing of Fraud Diamond Theory Based on Local Wisdom on Fraud Behavior

Abstract: This study aims to examine the elements of fraud diamond theory based on local wisdom on fraud behavior. This research was conducted in all universities in Buleleng Regency, Bali. This research uses a quantitative method by using 40 finance department employees in all universities in Buleleng Regency as respondents. The results of this study are that before moderating variable Tri Kaya Parisudha presents, all independent variables namely pressure, opportunity, rationalization and capacity have positive effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Rationalization is a thought that justifies an action as natural behavior, which can be accepted in normal society (Sujana, Yasa, & Wahyuni [22]). Slezak (Said, et al [21]) says rationalization is a way to legitimize an action that is not in accordance with one's beliefs.…”
Section: Rationalizationmentioning
confidence: 99%
“…Rationalization is a thought that justifies an action as natural behavior, which can be accepted in normal society (Sujana, Yasa, & Wahyuni [22]). Slezak (Said, et al [21]) says rationalization is a way to legitimize an action that is not in accordance with one's beliefs.…”
Section: Rationalizationmentioning
confidence: 99%
“…In this study, the relationship between the Tri Kaya Parisudha philosophy is thought to be able to control individual behavior, so that the level of Tri Kaya Parisudha in the auditor can weaken the influence of the time pressure experienced by the auditor in carrying out his duties, so as to pressure the auditor to ignore audit procedures that should be done in the form of premature termination. audit procedures (I. G. P. E. R. Dewi, 2019;Sujana et al, 2019). Auditors with a high level of Tri Kaya Parisudha in themselves will not fall for it to prematurely terminate the audit procedure even in conditions of time pressure.…”
Section: Boundmentioning
confidence: 99%
“…Auditors with a high level of Tri Kaya Parisudha in themselves will not fall for it to prematurely terminate the audit procedure even in conditions of time pressure. Sujana et al, (2019) found that the application of the Tri Kaya Parisudha concept encourages accountability in the management of a non-profit organization. In addition, Sujana & Saputra (2020) conducted research on the ethical behavior of auditors, and found that Tri Kaya Parisudha was able to increase the ethical sensitivity of auditors.…”
Section: Boundmentioning
confidence: 99%
See 2 more Smart Citations